Bridging health and foreign policy: the role of health impact assessments - Kelley Lee; Alan Ingram; Karen Lock; Colin McInnes (The World Health Organization, 2007)
Health impact assessment (HIA) is an important tool for exploring the intersection between health and foreign policy, offering a useful analytical approach to increase positive health impacts and minimize negative impacts. Numerous subject areas have brought health and foreign policy together. Yet further opportunities exist for HIA to address a broader range of health impacts that otherwise may not be seen as relevant to foreign policy. HIA may also improve the quality of scientific evidence available to policy-makers. The Framework Convention on Tobacco Control offers lessons for the strategic use of HIA. However, HIA alone is limited in influencing these decision-making processes, notably when issues diverge from other core concerns such as economics and security. In such cases, HIA is an important tool to be used alongside the mobilization of key constituencies and public support.